ANALISIS PENGARUH PENGUNGKAPAN RISIKO PERUSAHAAN TERHADAP BIAYA MODAL EKUITAS DAN KINERJA PERUSAHAAN - Diah Riskanah; Agung Juliarto (Diponegoro Journal of Accounting, 2018)
This research aims to analyze the effect of corporate risk disclosure on cost of equity capital and firm perfomance. Measurement of cost of equity capital uses Olshon model. While company performance is measured using return on asset (ROA). This research uses risk disclosure index as a proxy for measuring corporate risk disclosure. The population of this research is manufacture companies listed on the Indonesia Stock Exchange (IDX) during 2014-2016 with a total sampel of 207. The methods of data collection used in this study is purposive sampling method. There are several control variables included in this study, such as systematic risk, unsystematic risk, leverage, firm size, board independence,consumer price index, market-to-book ratio, tobin’s q, audit committee independen, quality of external auditors. Ordinay least square regression analysis was used as the primary tool of analysis in this research.The results of this research show that corporate risk disclosure has a negative effect on cost of equity capital. However, corporate risk disclosure has not influenced firm perfomance (ROA).